On the myth of the Digital Natives and the Net Generation - Schulmeister, Rolf [Verfasser] (My University, 2013)
"Analyses of the frequency and type of media use in persons up to 30 years of age prove that the socalled Digital Natives do not exist. Their media use is a leisure pursuit only, and is not being transferred to learning; it principally serves the purpose of communication with peers, the most important part in the socialisation of young adults. Against this background, the article sheds light on the nature and function of media use in young adults and argues that the learners’ individual motives and dispositions most decisively influence the use of new media in learning contexts." (Autorenreferat, BIBB-Doku)
Keywords: L 4.1.2 Elektronische Medien; G 2.2.2 Internet / Mediengesellschaft; P 1.1 Jugendliche; Digitale Medien; Mediennutzung; Medienkompetenz; Lernverhalten; Jugendlicher; Digital Native